2020
DOI: 10.3389/fnhum.2019.00476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi Chuan on Inhibitory Control in Elderly Women: An fNIRS Study

Abstract: Background: Inhibitory control is a sub-ability of executive function and plays an important role in the entire cognitive process. However, declines in inhibitory control during aging significantly impair the quality of life of elderly people. Investigating methods to delay the decline of inhibitory control has become a focal point in current research. Tai Chi Chuan (TCC) is one effective method used to delay cognitive declines in older adults. However, the specific effects of TCC on inhibitory control and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 53 publications
(50 reference statements)
3
56
0
3
Order By: Relevance
“…A sufficient cognitive challenge seems to play a greater role in obtaining cognitive benefits than high doses of intervention sessions ( Gheysen et al, 2018 ). Although no changes in memory were observed, the tai chi intervention resulted in improved mental switching, inhibitory control, and visuospatial processing in older adults, and again these findings are in line with previous studies ( Sungkarat et al, 2017 ; Wu et al, 2018 ; Yang et al, 2020 ). There is evidence that tai chi induces structural and functional changes, which explain the observed behavioral changes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A sufficient cognitive challenge seems to play a greater role in obtaining cognitive benefits than high doses of intervention sessions ( Gheysen et al, 2018 ). Although no changes in memory were observed, the tai chi intervention resulted in improved mental switching, inhibitory control, and visuospatial processing in older adults, and again these findings are in line with previous studies ( Sungkarat et al, 2017 ; Wu et al, 2018 ; Yang et al, 2020 ). There is evidence that tai chi induces structural and functional changes, which explain the observed behavioral changes.…”
Section: Discussionsupporting
confidence: 91%
“…There is evidence that tai chi induces structural and functional changes, which explain the observed behavioral changes. Short-term regular Yang-style tai chi practice increases prefrontal cortex activation and this increase is associated with improvements in mental switching ( Wu et al, 2018 ) and inhibitory control ( Yang et al, 2020 ). Tao et al (2017b) found that the parahippocampal volume increased after tai chi practice, and it was also shown that the parahippocampal cortex is associated with visuospatial processing ( Aminoff et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pieramico et al pointed out that multi-modal exercise can be an effective strategy to prevent aging-related cognitive loss, and significant capability of functional and structural changes were maintained in older adults [45]. Other studies have shown that regular physical training may contribute to changes in brain structure [46], brain function [47,48], and alleviate age-related cognitive decline [49]. In the majority of exercise cognition imaging studies, researchers have focused on short-term effects rather than prolonged cognitive benefits of exercise, particularly for motor-cognitive exercise training such as tai chi chuan that is culturally suitable for Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous cross-sectional and cohort studies 3,37 , our study found that Hong chuan Tai Chi practitioners had better global cognitive status than Tai Chi-naïve controls. Although in this study a causal relationship cannot be assumed as many randomized controlled trials did 33,[41][42][43] , it still suggested a close association between Tai Chi practicing and cognitive benefits. A meta-analysis of executive function in randomized controlled trials of cognitively healthy adults indicated a large effect size induced by Tai Chi compared with controls and a moderate effect size compared with other exercise controls 5 .…”
Section: Chi Group Demonstrated Better Performance In Mini-mental Stamentioning
confidence: 59%